DEVELOPMENT OF A TEXTBOOK FOR THE COURSE FUNDAMENTAL CONCEPTS OF CIVIC EDUCATION BASED ON DEEP LEARNING IN THE PRIMARY SCHOOL TEACHER EDUCATION PROGRAMME (PGSD), FACULTY OF TEACHER TRAINING AND EDUCATION (FKIP), MUSAMUS UNIVERSITY - rival hanip; andhika wahyudiono; Rudolfus Ruma Bay; Lay Riwu; Yonarlianto Tembang; Riskiria Yulianti (SOSIOEDUKASI, 2026)
The teaching of Civic education in primary schools is still dominated by a rote-learning approach that overlooks the development of student character. This issue is compounded by the use of monotonous lecture methods and the limited ability of teachers to connect the subject matter with local contexts. This study aims to develop a textbook for the Basic Concepts of Civic education course based on Deep Learning at the Primary School Teacher Education (PGSD) department, Faculty of Teacher Training and Education (FKIP), Musamus University, which is feasible for use. It also seeks to test its effectiveness in enhancing students' conceptual understanding and critical thinking skills through the integration of Pancasila values and the local wisdom of Papua. The research employed a Research and Development approach utilising the 4-D model, involving subject matter experts, media experts, learning experts, and students through individual trials, small-group trials, and field trials. The results showed that the textbook obtained an average feasibility score of 75.9 per cent across all validation and trial stages, categorised as 'feasible'. User responses provided positive assessments, with an average score of 71.5 per cent, indicating the practicality and effectiveness of the textbook in promoting deep conceptual understanding. The study concludes that the Deep Learning-based textbook is feasible for use and is capable of strengthening students' national character. It is recommended that the textbook be implemented more widely, further developed by incorporating digital technologies such as augmented reality, and supported by institutional policies to ensure the sustainability of this learning innovation.